2018
DOI: 10.11646/phytotaxa.372.1.1
|View full text |Cite
|
Sign up to set email alerts
|

The Encyclia ambigua complex (Laeliinae, Orchidaceae), a synopsis and notes on Encyclia virens and Epidendrum alatum

Abstract: A synopsis of the Encyclia ambigua complex, a member of the E. ceratistes clade, is presented. It is composed of three species, namely E. ambigua, E. trachychila, and E. dressleri. These taxa are restricted to the southern part of Megamexico in Mexico, Guatemala, Honduras, and Nicaragua and occur mostly in oak-pine or broadleaf evergreen forests, or more rarely, in tropical dry forests at elevations of (600–)1,250–1,700(–2,000) m. The recently described Encyclia alborubra is treated as a synonym of E. ambigua.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Encyclia s.s. (sensu Higgins et al [ 2 ]) can be characterized by a lip bearing a cymbiform callus and a variable apex and column with two lateral wings (= staminodes) and an elongate filament giving the gynostemium an appearance of the three-toothed apex. Recent phylogenetic analysis of the genus utilizing nuclear and plastid DNA sequences [ 19 21 ] revealed that Encyclia is composed of lineages that are strongly correlated geographically, with some clades fully restricted to particular biogeographical areas of Neotropics. These clades are confined to such areas as Megamexico II (e.g., the E. adenocarpos clade), the extra-Megamexican portion of the Central American Isthmus (Costa Rica and Panama; e.g., the E. mooreana alliance), the West Indies (e.g., the E. plicata alliance), northern South America, the Andean foothills, the Guiana Shield, the Amazon Basin, or several areas of Brazil (e.g., the E. argentinensis alliance) such as the Mata Atlantica, the Cerrado, or the Caatinga ([ 21 ] and references therein).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Encyclia s.s. (sensu Higgins et al [ 2 ]) can be characterized by a lip bearing a cymbiform callus and a variable apex and column with two lateral wings (= staminodes) and an elongate filament giving the gynostemium an appearance of the three-toothed apex. Recent phylogenetic analysis of the genus utilizing nuclear and plastid DNA sequences [ 19 21 ] revealed that Encyclia is composed of lineages that are strongly correlated geographically, with some clades fully restricted to particular biogeographical areas of Neotropics. These clades are confined to such areas as Megamexico II (e.g., the E. adenocarpos clade), the extra-Megamexican portion of the Central American Isthmus (Costa Rica and Panama; e.g., the E. mooreana alliance), the West Indies (e.g., the E. plicata alliance), northern South America, the Andean foothills, the Guiana Shield, the Amazon Basin, or several areas of Brazil (e.g., the E. argentinensis alliance) such as the Mata Atlantica, the Cerrado, or the Caatinga ([ 21 ] and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…Recent phylogenetic analysis of the genus utilizing nuclear and plastid DNA sequences [ 19 21 ] revealed that Encyclia is composed of lineages that are strongly correlated geographically, with some clades fully restricted to particular biogeographical areas of Neotropics. These clades are confined to such areas as Megamexico II (e.g., the E. adenocarpos clade), the extra-Megamexican portion of the Central American Isthmus (Costa Rica and Panama; e.g., the E. mooreana alliance), the West Indies (e.g., the E. plicata alliance), northern South America, the Andean foothills, the Guiana Shield, the Amazon Basin, or several areas of Brazil (e.g., the E. argentinensis alliance) such as the Mata Atlantica, the Cerrado, or the Caatinga ([ 21 ] and references therein). Only a few lineages of Encyclia (e.g., the Encyclia ceratistes species complex), and only a handful of species (e.g., Encyclia cordigera (Kunth) Dressler) occur in two or more of these major areas [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation